Development of INSANG (Interaksi Sosial Anak Sekarang) Poster in Improving Social Skills - Qothrunnadaa Salsabila; Cucun Sunaengsih; Dadan Nugraha (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The decline in social interactions within the school environment has a significant impact on students' social skills. The purpose of this research is to enhance the importance of developing social skills among elementary school students in the digital era through a creative approach when creating a poster with the theme "INSANG," utilizing digital technology in the process. The Design and Development (D&D) method and the ADDIE research model are employed as guides in development, supported by a descriptive quantitative approach. The research sample was taken from 29 fifth-grade students of SDN Perumnas Suradita in Tangerang Regency, with the implementation of pretest and posttest instruments to measure changes in social skills. Data analysis results using the Paired Samples T-Test show a significant difference with a significance value (2-tailed) of 0.038 (p < 0.05), indicating that the development of the INSANG poster effectively enhances students' social skills with the assistance of digital technology. This research provides valuable insights into addressing the challenges of developing social skills amidst the digital era while emphasizing the crucial role of technology in creating innovative and creative learning media.